1999
DOI: 10.1021/bi990335x
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of the Adenine-DNA Glycosylase MutY Confers Specificity for 8-Oxoguanine·Adenine Mispairs and May Have Evolved from MutT, an 8-Oxo-dGTPase

Abstract: MutY is an adenine-DNA glycosylase with specificity for mismatches involving 8-oxoguanine (oG.A) or guanine (G.A). In addition to a 25 kDa catalytic domain common to all members of its DNA glycosylase superfamily, MutY has a 14 kDa C-terminal domain. Sequence analyses suggest that this C-terminal domain is distantly related to MutT, a pyrophosphohydrolase specific for 2'-deoxy-8-oxoguanosine triphosphate (doGTP). Here we present biochemical evidence that the MutT-like domain of MutY is the principal determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
127
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 36 publications
14
127
2
Order By: Relevance
“…Over a short reaction period the rate of cleavage of calf mtMYH was much faster for the A/8-oxoG mismatch than other substrates. This substrate reactivity is similar to that of E.coli MutY (2,57,58). In view of the fact that mitochondrial OGG1-like protein will cleave 8-oxoG-containing mismatches and not mismatches paired with G, it is of biological importance that mtMYH binds tightly to A/8-oxoG mismatches but not A/G or A/C mismatches.…”
Section: Discussionsupporting
confidence: 53%
“…Over a short reaction period the rate of cleavage of calf mtMYH was much faster for the A/8-oxoG mismatch than other substrates. This substrate reactivity is similar to that of E.coli MutY (2,57,58). In view of the fact that mitochondrial OGG1-like protein will cleave 8-oxoG-containing mismatches and not mismatches paired with G, it is of biological importance that mtMYH binds tightly to A/8-oxoG mismatches but not A/G or A/C mismatches.…”
Section: Discussionsupporting
confidence: 53%
“…The C-terminal domain has sequence (58) and structural homology to the d(OG)TPase MutT (59), indicating a role in recognition of OG. Kinetic experiments with substrates and binding assays with substrate analogs are consistent with a role of the C-terminal domain in OG recognition and nucleotide flipping (58,60). However, it is possible that this domain has additional functions.…”
supporting
confidence: 60%
“…A-containing DNA-We (60) and others (58,67) have previously shown that removal of the C-terminal domain to form a truncated enzyme (henceforth referred to as Stop 225) affects the intrinsic rate for adenine removal. However, Stop 225 retains biphasic kinetic behavior under conditions of substrate excess, indicating that the rate of product release remains rate-limiting in a manner similar to that observed with the WT enzyme (60).…”
Section: Endo IV Does Not Significantly Increase the Product Release mentioning
confidence: 99%
“…The N-terminal domain of E. coli MutY has the catalytic activity (36 -40); however, the C-terminal domain is important for GO recognition (36,37,40,41). The PCNA binding motifs located at the Cterminal ends of eukaryotic MYH are not conserved in bacterial MutY proteins.…”
Section: The Interactions Between Myh and Pcna Proteins From Both S mentioning
confidence: 99%